Heart Rate Variability and Exceptional Longevity - Hernández-Vicente, Adrián; Hernando, David; Santos-Lozano, Alejandro; Rodríguez-Romo, Gabriel; Vicente-Rodríguez, Germán; Pueyo, Esther; Bailón, Raquel; Garatachea, Nuria (Frontiers in Physiology, 2020)
Centenarians are the paradigm of human extreme longevity and healthy aging, because they have postponed, if not avoided, mayor age-related diseases. The purpose of this study was to investigate potential differences in resting heart rate variability (HRV) between young adults, octogenarians and centenarians and assess whether HRV variables are predictors of all-cause mortality in centenarians. To this end, three groups of participants: young adults (N=20; 20.6±2.3 years), octogenarians (N=18; 84.1±2.6 years), and centenarians (N=17; 101.9±1.9 years) were monitored for 15 min at rest (seated, without moving or talking) to measure RR intervals, from which HRV was evaluated. Our results showed a clear decrease with age in the main parasympathetic HRV variables, as well as in the standard deviation of the RR series (SDNN) and in low frequency (LF) heart rate oscillations, although differences between octogenarians and centenarians did not reach statistical significance. In 14 centenarians followed until death, only SDNN showed significant correlation (ρ=0.536; p=0.048) with survival prognosis. Additionally, SDNN <19 ms was associated with early mortality (≤1 year) in centenarians (Hazard Ratio=5.72). In conclusion, HRV indices reflecting parasympathetic outflow as well as SDNN and LF all present an age-related reduction, which could be representative of a natural exhaustion of allostatic systems related to age. Moreover, low SDNN values (<19 ms) could be associated with early mortality in centenarians. HRV seems to play a role in exceptional longevity, which could be accounted for by centenarians’ exposome.